2013
DOI: 10.1093/inthealth/iht022
|View full text |Cite
|
Sign up to set email alerts
|

Current sickle cell disease management practices in Nigeria

Abstract: The care available for SCD in Nigeria is still suboptimal and there is an urgent need for concerted effort to tackle the problem, but to make a significant impact on the burden of the disease would require more focus at the primary care level. Some steps to achieving this are outlined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
104
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(120 citation statements)
references
References 30 publications
6
104
1
Order By: Relevance
“…This was not unexpected as the study participants were unmarried youths compared to current study among married adults. A higher proportion of respondents in this study was aware and correctly identified their genotype in comparison to only 55 % awareness among respondents in a recent study in the same population (Galadanci et al 2014). However, the study was conducted among all mothers and not specifically mothers who have a child with sickle cell anemia.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…This was not unexpected as the study participants were unmarried youths compared to current study among married adults. A higher proportion of respondents in this study was aware and correctly identified their genotype in comparison to only 55 % awareness among respondents in a recent study in the same population (Galadanci et al 2014). However, the study was conducted among all mothers and not specifically mothers who have a child with sickle cell anemia.…”
Section: Discussioncontrasting
confidence: 80%
“…In Nigeria, the prevalence SCT is estimated at 24 % (Taiwo et al 2011;WHO 2006). It is estimated that there are more than 40 million individuals who carry the sickle cell trait in Nigeria and more than 150,000 children born each year with SCA (Galadanci et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Estimates put SCD prevalence between 2 and 3%, in a population of 170 million Nigerians [2][3][4] . Low levels of awareness/ knowledge, poor case finding strategies and sub-optimal treatment continue to fuel morbidity and mortality rates in the country [5][6][7][8][9] . The introduction of novel agents such as hydroxyurea has greatly impacted on disease outcome in developed climes such as US [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, no patient had penicillin prophylaxis, a practice not in keeping with internationally accepted guidelines37. In a recent Nigerian study conducted across 18 sickle cell clinics, only eight of them routinely gave prophylactic penicillin38. This is in contrast to a study conducted in Brazil where 76.1% of the patient population received penicillin prophylaxis39.…”
Section: Discussionmentioning
confidence: 78%